The future ain’t what it used to be: Growth models, structural change, and history - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2016)
In this paper I focus only on medium- to long-term trends for economic growth, considering first the global historical experience and discussing then projections for future growth utilized in some important exercises of prospective. A conclusion is that many projections suggest further acceleration of world economic growth at levels that do not seem to be in line with historical experience. This paper then speculates about possible reasons for that discrepancy.